To trace or not to trace: Saving lives from COVID-19 at the cost of privacy breach in Bangladesh - Tanvir Alam (638619) (2020)
The World Health Organization declared the novel coronavirus disease 2019 (COVID-19) outbreak as a pandemic on March 12, 2020. Since the first official reported case of COVID-19 in Bangladesh on 08 March 2020,1 Bangladesh is now ranked 17th among the countries in the world in terms of positive COVID19 cases with more than 205,000 people testing positive for COVID-19 after diagnosis (as of 20 July, 2020).2 Without any effective therapeutic measures to control COVID-19, like many other countries, Bangladesh adopted a nontherapeutic measure to control this pandemic; however, there is ongoing debate on the implementation and effectiveness of such measurements. Other Information Published in: Qatar Medical Journal License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.5339/qmj.2020.35